Population genetic structure and gene flow of Adélie penguins (Pygoscelis adeliae) breeding throughout the western Antarctic Peninsula. Issue 6 (28th July 2017) - Gorman, Kristen B.; Talbot, Sandra L.; Sonsthagen, Sarah A.; Sage, George K.; Gravely, Meg C.; Fraser, William R.; Williams, Tony D.
Abstract: Adélie penguins ( Pygoscelis adeliae ) are responding to ocean–climate variability throughout the marine ecosystem of the western Antarctic Peninsula (WAP) where some breeding colonies have declined by 80%. Nuclear and mitochondrial DNA (mtDNA) markers were used to understand historical population genetic structure and gene flow given relatively recent and continuing reductions in sea ice habitats and changes in numbers of breeding adults at colonies throughout the WAP. Genetic diversity, spatial genetic structure, genetic signatures of fluctuations in population demography and gene flow were assessed in four regional Adélie penguin colonies. The analyses indicated little genetic structure overall based on bi-parentally inherited microsatellite markers ( F ST =-0.006–0.004). No significant variance was observed in overall haplotype frequency (mtDNA Φ ST =0.017; P =0.112). Some comparisons with Charcot Island were significant, suggestive of female-biased philopatry. Estimates of gene flow based on a two-population coalescent model were asymmetrical from the species' regional core to its northern range. Breeding Adélie penguins of the WAP are a panmictic population and hold adequate genetic diversity and dispersal capacity to be resilient to environmental change.